(untitled) (MINDEN Journal of History and Archaeology, 2024)
This essay discusses the writing of state history in Malaysia which began at the turn of the 20th century through local scholar officials followed by British scholar officials before Buyong Adil joined the fray in the early 1940s. In the 1970s and 1980s Buyong went on the develop his state history and have 12 of them published by Dewan Bahasa and Pustaka. For unknown reasons only Kelantan was left out. However, Buyong’s state history and even those of the British scholar officials had nothing much on the laity while it possible to write a more comprehensive state history covering economic, political and social history and culture. As suggested for Pahang the new state history needs to be more comprehensive and inclusive. After 1888 there are much more sources including annual reports (1888-1939) which is crucial in understanding Pahang’s development or underdevelopment under colonial rule, the Pahang uprising, the 1926-27 floods that destroyed much of the state, and the labouring classes of the 1930s. There are much more sources on the period after 1945 with documentary materials located at the National Archives of Malaysia, Kuala Lumpur and the National Archives of Malaysia Pahang state. A judicious use of these sources could produce a state history for Pahang that would be a big improvement of Buyong’s work or those of British scholar officials. Keywords: state history; scholar officials; Buyong Adil; laity; economy; archival sources